Decentralization of leprosy control actions in the micro-region of Almenara, State of Minas Gerais (Revista Latino-Americana de Enfermagem, 2011)
This study analyzes the decentralization process of Leprosy control actions for Family Health Strategy units in the cities of the Almenara micro-region, in the state of Minas Gerais, Brazil. This qualitative research, based on the concept "Technological Organization of Work", was carried out in nine municipalities. Semi-structured interviews and document research were used for data collection. Forty-five interviews with care providers and health managers were conducted. The data collection took place between November 2007 and February 2008. Content Analysis was utilized to study the data and results indicate that the cities present different levels of decentralization and that the process was determined based on local specifications and on the engagement of care providers and health managers. Several cities kept a reference team to provide support to primary health care. The conclusion is that the decentralization process is a strategy that proves to be useful in facing Leprosy in the micro-region.